KEDUDUKAN PEMERIKSAAN SETEMPAT OLEH HAKIM DALAM PEMBUKTIAN PERSPEKTIF HUKUM ACARA PERDATA - TITIN APRIANI (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this study is to find out how the position of local examinations carried out by judges in proving the perspective of civil procedural law and what are the obstacles and the level of difficulty faced by judges in Indonesia in conducting local examinations. This research is library research, namely using data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is to collect various ideas, theories and concepts from various literature that focuses on the process comparison between the arguments, articles or other laws. The approach method used in this research is the statutory approach and the conceptual approach. The results of the study show that the position of local examinations carried out by judges in the perspective of civil procedural law is very appropriate to be carried out if it is deemed necessary and reasonable to carry out the provisions in the SEMA to conduct local inspections in order to avoid difficulties in carrying out the execution of decisions at a later date and there are arrangements in place. in HIR and Rbg.